SCREENING OF GENOTYPES FOR ALTERNARIA BLIGHT RESISTANCE IN SUNFLOWER (HELIANTHUS ANNUUS. L) - VENKATA R. PRAKASH REDDY; H. L. NADAF; A. G. VIJAYAKUMAR (The Bioscan, 2014)
An investigation was undertaken was undertaken to assess the magnitude of resistance to Alternaria blight using new interspecific derived lines. The material consisted of four cytoplasmic male sterile (CMS) lines and 12 restorer lines crossed in all possible combinations during summer 2011. Total of 16 parents and 48 hybrids along with four check hybrids were evaluated in randomized block design with two replications at MARS, Dharwad during kharif2011. At flowering stage, among the 16 parents, CMS-17A, PS-1070 and ID-25 shown moderate resistance reaction and among 48 hybrids, CMS-17A ´ PS1070 and CMS-17A ´ ID-25 showed moderate resistance reaction. At maturity stage, although, none of the parents showed tolerant to Alternaria leaf spot reaction while only one hybrid CMS-17A ´ PS1070 recorded some degree of tolerant reaction. Among the parents, CMS-17A and PS-1070 recorded lowest ‘r’ value and AUDPC value and CMS-607A and RES- 834-1 recorded highest ‘r’ value and AUDPC value and among the hybrids, CMS-17A based hybrids recorded the lowest ‘r’ value and AUDPC value indicates the slow blighters. Among the 48 hybrids, CMS-17A ´ PS1070, CMS-17A ´ ID-25 and CMS-1030A ´ ID-25 were recorded as potential hybrids for yield and Alternariadisease reaction.